Inertization of metals and hydrogen production as a byproduct from water hyacinth and water lettuce via plasma pyrolysis - Raynard Christianson Sanito; Cindy Lidwina; Hsi-Hsien Yang; Ya-Fen Wang (Heliyon, 2022)
Water hyacinth and water lettuce have been extensively used for phytoremediation of metals and metalloids. However, the reasonable disposal of phytoremediation plants is a difficult problem. This study aims to reduce metals and metalloids from water hyacinth and water lettuce, and produce hydrogen (H2) and methane (CH4) via an atmospheric-pressure microwave plasma reactor based on the circular economy concept. Inertization of metals and metalloids can be obtained by more than 60% for both water hyacinth and water lettuce. H2 and CH4 production of water hyacinth and water lettuce were 56.28%/57.30% and 3.75%/2% of volume fractions, respectively. Furthermore, total VOCs concentrations from the effluent gas were detected only at the values of 0.511% (water hyacinth) and 0.08% (water lettuce) of volume fractions, respectively. Overall, water hyacinth and water lettuce treated by atmospheric-pressure microwave plasma showed the potential of H2 and CH4 production as a by-product for alternative energy and inertization of metals/metalloids for the phytoremediation plants.